“Diseño de una estructura metálica con un puente grúa para el área de mantenimiento y bodega en la empresa Pulpa Moldeada S.A.” - Tisalema Tasigchana, Pedro Fidel (2024)
The company Pulpa Moldeada S.A. is affected by delays in the maintenance area due to the difficulty of operating with heavy equipment, and it causes delays in the maintenance schedules of motors and reducers, directly impacting the efficiency of the production line. For this reason, it was developed a design of a metallic structure and an electromechanical lifting and mobility system to improve the response time of the maintenance area. The design method based on Load and Resistance Factors, the design and stability of the bridge crane against variable loads is guaranteed. Key parameters, such as load requirements and maintenance times, were identified before approaching the design. Based on the recommendations of the Ecuadorian standard NEC-2015, a finite element analysis was performed with SAP2000 and ANSYS to evaluate the behavior of the gantry crane. It intended to avoid unplanned stops of the production line, requiring an investment of about $12275.64 for its implementation, expected to improve 15% of maintenance times and a progressive return on investment in a time of three years with nine months and 15 days, depending on the hoisting system implemented. The nominal capacity of the system is 29080 kg (29 t) and a safety factor of 3.125, taking into account the dynamic combination of study (D+L+LT), allowing in this infrastructure the installation of different fixed-mobile lifting systems, without exceeding the design capacity of 1000kg for the bridge crane and 18720 kg, for the warehouse.